The Invasion of Exotic Reptiles and Amphibians in Florida - Frank J. Mazzotti; Rebecca G. Harvey (EDIS, 2012)
Florida has more introduced species of reptiles and amphibians living and breeding in the wild than anywhere else in the world. This 6-page fact sheet summarizes findings from three recent scientific papers describing who these invaders are, their potential ecological impacts, and recommendations for their management and control. Written by Frank J. Mazzotti and Rebecca G. Harvey, and published by the UF Department of Wildlife Ecology and Conservation, May 2012.